A permissioned blockchain enabled trustworthy and incentivized emission trading system. (15th May 2022) - Muzumdar, Ajit; Modi, Chirag; Vyjayanthi, C.
Abstract: The emission trading systems (ETSs) have encouraged the more usage of renewable energy, aiming for energy generation. However, the existing ETSs suffer from carbon credit scams, poor monitoring, verification and reporting (MRV), participants' unwillingness and non-transparent trading. To address these issues, we propose a trustworthy and incentivized emission trading system using hyperledger (a permissioned blockchain) and smart contracts. It assures a transparent trading of carbon credits (CC) with better MRV. It applies three smart contracts viz; CC selling, CC buying and CC trading to achieve reliable and secure transactions of the energy trading with the improved trust. For emission trading, we propose a priority based auction, in which priority to CC sellers is assigned based on their carbon credits, while priority to CC buyers is assigned based on their reputation. This strategy rewards the participants for their efforts towards avoiding the deforestification and the use of renewable energy. In addition, it is incentivized for both CC buyers as well as sellers, and thus, it encourages more number of participants. The proposed system satisfies more than 84.37% bids with minimum transaction latency (0.41 s) and sufficient throughput (102.42 tps). In addition, multi-criteria analysis using different statistical methods is performed to evaluate and compare the effectiveness of the proposed systems. Highlights: Design and implementation of blockchain enabled emission trading system. Priority based trading for fair and incentivized trading of carbon credits. Mathematical modeling and analysis of participants' payoff in emission trading. Satisfying more number of bids with low latency and high throughput. Higher effectiveness than the existing works as per multi-criteria analysis.